ANTIMICROBIAL POTENTIAL OF SILVER NANOPARTICLES SYNTHESIZED USING ULVA RETICULATA - DEVI, J. SARANIYA; BHIMBA, B. VALENTIN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Production and application of silver nanoparticles (AgNPs) is an emerging field of research. The present study was demonstrated with rapid synthesis of AgNPs using marine macroalgae-Ulva reticulata. The observation of prominent colour change at 121ÂºC within 10 mins indicates the formation of AgNPs. The synthesized AgNPs were characterized by UV-Vis spectrum, Energy Dispersive Spetrum (EDS), Fourrier Transform Infra Red spectroscopy (FTIR) and Transmission Electron Microscopy (TEM). The aim of the study is to evaluate the antibacterial and antifungal activity of synthesized AgNPs. Antibacterial activity was tested against Gram positive Staphylococcus aureus, and Gram negative Escherichia coli, Pseudomonas aeruginosa, Bacillus sp., Klebsiella pneumoniae. Antifungal activity was tested against Candida albicans, Candida parapsilosis and Aspergillus niger. AgNPs were fairly toxic to Bacillus sp.and Staphylococcus aureus with the inhibition zone of 26 and 25mm. AgNPs revealed higher antifungal activity against Candida albicans, Candida parapsilosis and Aspergillus niger with inhibition zone of 36, 30 and 30mm.Key words:Silver nanoparticles, Marine maro algae-Ulva reticulata, antibacterial, antifungal activity.